LINGKUNGAN NON FISIK KANTOR: MEMBANGUN KEHARMONISAN, KOMUNIKASI, DAN MOTIVASI KERJA DI LINGKUNGAN PESANTREN AL-IHSAN BOARDING SCHOOL RIAU - Imam Ma’arif; Irawati; Nadia Nabila; Rinda Luftia Kaysa; Zaskia Adella Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The non-physical office environment plays an important role in creating a harmonious, comfortable, and productive workplace. This study aimed to describe the non-physical work environment at Al-Ihsan Boarding School Riau, focusing on work relationships, communication, and employee motivation. The research employed a descriptive qualitative approach using observation and interview techniques. The findings revealed that harmonious relationships between leaders and employees were established through open and effective communication. Communication among employees also supported teamwork and task implementation. A supportive work atmosphere contributed to employee comfort and job satisfaction. In addition, leaders regularly provided motivation and positive guidance to enhance employee performance. Conflict resolution was conducted through problem identification and collaborative discussion, while workplace comfort was maintained through good service practices and adherence to standard operating procedures (SOPs). Overall, the non-physical office environment at Al-Ihsan Boarding School Riau contributed significantly to fostering harmonious relationships, effective communication, and strong work motivation among employees.